DIAGNÓSTICO TÉCNICO-SANITÁRIO DE TRÊS UNIDADES DE PRODUÇÃO DE LEITE DO MUNICÍPIO DE PANAMBI-RS - Henriques, Angélica d. O.; Uhde, Leonir T.; Mumbach, Tatiele; Carbonera, Roberto; Martins, Luciane R. V. (Salão do Conhecimento, 2013)
Resumo